Late tectonic reorientation of lineaments and fabrics in the northern Eastern Ghats Province, India: Evaluating the role of the Mahanadi Shear Zone. (1st October 2020) - Bose, Subham; Das, Arijit; Samantaray, Suvankar; Banerjee, Swaraj; Gupta, Saibal
Highlights: Lineament trends become WNW-ESE in the northern Eastern Ghats Province (EGP). D1 and D2 granulite facies fabrics in the EGP are generally parallel to lineaments. D3 extensional deformation in amphibolite facies rotated early fabrics. D4 dextral shearing along Mahanadi Shear Zone operated in greenschist facies. D3 extension operated between 730 and 680 Ma. Abstract: South of the MSZ that cuts across the Eastern Ghats Province (EGP) of India, lineament trends and early granulite facies fabrics rotate from NNE-SSW in the south towards the WNW-ESE striking, northerly dipping Mahanadi Shear Zone (MSZ) in the north. Using field, microstructural and EBSD techniques, we demonstrate that D1 and D2 planar fabrics are reoriented by an E-W trending, northerly dipping D3 extensional shear zone that has a subordinate sinistral, strike-slip component. D3 microstructures are pervasive, with quartz and feldspar microstructures characteristic of amphibolite facies metamorphism. Monazite chemical ages from the D3 shear zone yield ages in the range 730–680 Ma. The MSZ, representing D4 deformation in the area, is a predominantly dextral strike-slip deformation. During D4, microstructures evolve exclusively through plastic deformation of quartz and culminates in S4 mylonitic fabric formation in high D4 strains zones under greenschist facies conditions. These microstructures are restricted to the MSZ and localized high D4 strain zones, unlike the D3 microstructures. We conclude that the earlier, post-granulite extensional deformation D3, and not the MSZ, was responsible for the swing in lineament and fabric trends in the northern EGP.